Impact of a telemedicine system on work burden and mental health of healthcare providers working with COVID-19: a multicenter pre-post prospective study. Issue 2 (25th May 2022) - Kagiyama, Nobuyuki; Komatsu, Takayuki; Nishikawa, Masanori; Hiki, Makoto; Kobayashi, Mariko; Matsuzawa, Wataru; Daida, Hiroyuki; Minamino, Tohru; Naito, Toshio; Sugita, Manabu; Miyazaki, Kunihisa; Anan, Hideaki; et al.
Abstract: Background: The coronavirus disease 2019 (COVID-19) pandemic impacts not only patients but also healthcare providers. This study seeks to investigate whether a telemedicine system reduces physical contact in addressing the COVID-19 pandemic and mitigates nurses' distress and depression. Methods: Patients hospitalized with COVID-19 in 4 hospitals and 1 designated accommodation measured and uploaded their vital signs to secure cloud storage for remote monitoring. Additionally, a mat-type sensor placed under the bed monitored the patients' respiratory rates. Using the pre-post prospective design, visit counts and health care providers' mental health were assessed before and after the system was introduced. Results: A total of 100 nurses participated in the study. We counted the daily visits for 48 and 69 patients with and without using the telemedicine system. The average patient visits were significantly less with the system (16.3 [5.5–20.3] vs 7.5 [4.5–17.5] times/day, P = .009). Specifically, the visit count for each vital sign assessment was about half with the telemedicine system (all P < .0001). Most nurses responded that the system was easy to use (87.1%), reduced work burden (75.2%), made them feel relieved (74.3%), and was effective in reducing the infection risk in hospitals (79.1%) and nursing accommodations (95.0%). Distress assessed by Impact of Event Scale-Revised and depression by Patient Health Questionnaire-9 were at their minimum even without the system and did not show any significant difference with the system ( P = .72 and .57, respectively). Conclusions: Telemedicine-based self-assessment of vital signs reduces nurses' physical contact with COVID-19 patients. Most nurses responded that the system is easy and effective in reducing healthcare providers' infection risk. Lay Summary: In this multicenter pre-post prospective study, we investigated whether a telemedicine system reduces physical contact in addressing the coronavirus disease 2019 (COVID-19) pandemic and mitigates nurses' mental stress. We counted the daily patient visits before and after using a telemedicine system, with which patients uploaded their vital signs for remote monitoring. Simultaneously, a mat-type sensor for monitoring respiratory rates was also introduced. The average patient visits were less for 69 patients treated with the system than 48 treated without it (16.3 vs 7.5 times/day, P = .009). Specifically, the visit count for each vital sign assessment was about half (all P < .0001). A total of 100 nurses answered to a questionnaire and many responded that the system was easy to use (87.1%), reduced work burden (75.2%), made them feel relieved (74.3%), and was effective in reducing the infection risk in hospitals (79.1%) and nursing accommodations (95.0%). Distress assessed by Impact of Event Scale-Revised and depression by Patient Health Questionnaire-9 were at their minimum even without the system and did not change with the system ( P = .72 and .57, respectively). Thus, the telemedicine system reduced physical contacts and nurses had favorable impression to the system despite no significant improvement in mental stress scores.